Crop-livestock integration provides opportunities to mitigate environmental trade-offs in transitioning smallholder agricultural systems of the Greater Mekong Subregion - Paul, Birthe K.; Epper, C.A.; Tschopp, D.J.; Long, C.T.M.; Tungani, V.; Burra, Dharani Dhar; Hok, L.; Phengsavanh, P.; Douxchamps, Sabine (Elsevier, 2022)
CONTEXT The Greater Mekong Subregion has been undergoing rapid agricultural transformation over the last decades, as traditional diverse subsistence-oriented agriculture is evolving towards intensified commercial production systems. Negative environmental impacts often include deforestation, nutrient pollution, and greenhouse gas (GHG) emissions.